In Vivo Respiratory-Gated Micro-CT Imaging in Small-Animal Oncology Models - Dawn Cavanaugh; Evan Johnson; Roger E. Price; Jonathan Kurie; Elizabeth L. Travis; Dianna D. Cody (Molecular Imaging)
Micro-computed tomography (micro-CT) is becoming an accepted research tool for the noninvasive examination of laboratory animals such as mice and rats, but to date, in vivo scanning has largely been limited to the evaluation of skeletal tissues. We use a commercially available micro-CT device to perform respiratory gated in vivo acquisitions suitable for thoracic imaging. The instrument is described, along with the scan protocol and animal preparation techniques. Preliminary results confirm that lung tumors as small as 1 mm in diameter are visible in vivo with these methods. Radiation dose was evaluated using several approaches, and was found to be approximately 0.15 Gy for this respiratory-gated micro-CT imaging protocol. The combination of high-resolution CT imaging and respiratory-gated acquisitions appears well-suited to serial in vivo scanning.